Limit equilibrium of the piece-homogeneous elastic body with interfacial shear cracks at the corner point of the media-separating boundary - Nazarenko, V.M.; Kipnis, A.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
The limit equilibrium of the piece-homogeneous isotropic elastic body with an interfacial shear crack at the corner point of the media-separating boundary is investigated. The exact solution of the corresponding problem of the theory of elasticity for a wedge-shaped body is constructed by the Wiener—Hopf method.